The prevalence of thrombocytopenia in pregnant women in Baghdad: single centre study - Muhammad, Eaman M.; Sabri, Ekhlass H.; Saeed, Hussam D. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: The prevalence of thrombocytopenia in most studies ranges from 7 to 10% of allpregnant females. Although pregnancy is associated with physiological changes that may affectplatelet count, several pathological conditions can cause thrombocytopenia which have a significantimpact on both the mother and her baby.Objective: The aim of this study was to determine the prevalence of thrombocytopenia in pregnantwomen attending an out-patient clinic in Al-Yarmouk Teaching hospital in Baghdad.Material and Methods: A cross sectional study conducted at Al-Yarmouk Teaching Hospital from1st October 2016 to 1st July 2017. Five hundred sixty pregnant women randomly selected as the studygroup and another 100 non-pregnant women as the control group were enrolled in this study. Acomplete blood count and blood film were done for both the selected groups.Results: Thrombocytopenia was found in 7.1% of the cases. The most common cause ofthrombocytopenia was gestational thrombocytopenia seen in 19(47.5%) patients and PE & HELLPsyndrome 9 (22.5%) patients. Most of our cases were asymptomatic and only one case developedheavy vaginal bleeding while there were 2 cases who had platelets below 50,000 considered as severethrombocytopenia without significant bleeding.Conclusion: Thrombocytopenia is not a rare condition in pregnancy. Accurate etiological diagnosis isessential for effective management. Most of the cases are mild, self-limiting and rarely cause withcomplications